2011
DOI: 10.1016/j.jacc.2011.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Cost-Effectiveness of Computed Tomography Screening for Coronary Artery Calcium in Asymptomatic Individuals

Abstract: Screening for coronary artery calcium with CT in individuals at intermediate risk of CHD is probably cost-effective in men but is unlikely to be cost-effective in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…15 The clinical relevance and whether a strategy including CT examinations is cost-effective are yet to be explored. 34 However, for CAC this improvement in prediction of cardiovascular outcomes (including mortality) has previously been established, [35][36][37] and has become the basis for trials on its use as screening tool for cardiovascular disease. 38 We found that AAC might represent a better reflection an individual's total burden of atherosclerosis, and that it further improved the performance of a prediction model for mortality, which already included CAC.…”
Section: Downloaded Frommentioning
confidence: 99%
“…15 The clinical relevance and whether a strategy including CT examinations is cost-effective are yet to be explored. 34 However, for CAC this improvement in prediction of cardiovascular outcomes (including mortality) has previously been established, [35][36][37] and has become the basis for trials on its use as screening tool for cardiovascular disease. 38 We found that AAC might represent a better reflection an individual's total burden of atherosclerosis, and that it further improved the performance of a prediction model for mortality, which already included CAC.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The report in this issue of the Journal by van Kempen et al (9) addresses the role of CAC testing in asymptomatic individuals with cost-effectiveness analysis (CEA) and comparative effectiveness analysis. Its primary conclusion is that screening for CAC with CT in individuals at intermediate risk of CHD is probably cost-effective in men but is unlikely to be cost-effective in women.…”
Section: See Page 1690mentioning
confidence: 99%
“…As a result, CAC testing could become less valuable in selecting patients for statin treatment and improving clinical outcomes. All of these scenarios lead to the conclusion that additional information beyond that available from the CEA by van Kempen et al (9) might be needed, before a convincing and definitive change in clinical practice guidelines would be justified.…”
Section: See Page 1690mentioning
confidence: 99%
See 2 more Smart Citations